ANALYSIS OF THEORY OF PLANNED BEHAVIOR (TPB) IN REALIZING THE HUMAN RESOURCES ENTREPRENEURSHIP (CASE STUDY ON MANAGEMENT STUDENTS OF STIE PELITA INDONESIA) - Astri Ayu Purwati; Angelina Angelina (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
Increasing number of population and limited employment causes a problem in Indonesia, namely unemployment. This has become the spotlight in various countries, as is the case with Indonesia. The aim of this research is for investigation the factors which have influence students’ interest at entrepreneurship. The models use planned behavior theory. Sampling was done by probability sampling technique with the simple random sampling. Data collection is carried out by distributing questionnaires which are directly distributed to respondents. This research involves 100 students from STIE Pelita Indonesia. This research used regression with t- test and analysis model SPSS 19 computer program. The results show that attitude, subjective norms, and perceived behavior control have influence and significant to intention entrepreneurship (at students of Pelita Indonesia).